Alkali-activated grouts based on slag-fly ash mixtures: From early-age characterization to long-term phase composition. (10th November 2020) - Aboulayt, Abdelilah; Souayfan, Faten; Roziere, Emmanuel; Jaafri, Reda; Cherki El Idrissi, Anass; Moussa, Redouane; Justino, Christophe; Loukili, Ahmed
Highlights: Grout mixtures based on sodium silicate activated slag and fly ash. Mixtures designed at high water-to-solid ratio of 0.75 are stabilized by xanthan gum. Early age reactivity and strength enhanced by fly ash substitution up to 40% Phase composition investigated at long-term through NMR-based analyses and models. C-A-S-H phase prevails over N-A-S-H gel up to 40% of fly ash. Abstract: Alkali-activation and the combination of slag and fly ash are expected to improve the chemical stability of grouts designed for underground works. Sodium silicate activated grout mixtures have been designed with a liquid activator volume fraction of 75%. As the data related to such high water-to-solid ratios are scarce, a comprehensive study has been designed in order to determine the phase composition of these grouts and thus understand the influence of fly ash proportion on engineering properties of grouts at both fresh and hardened states. The reactivity at early-age is mainly provided by slag with a drop in strength from 60% of fly ash. Nuclear magnetic resonance (NMR), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR) have been used to investigate the phase assemblage at long term (700 days). The alkali-activation of slag mainly produces a calcium silicate hydrate substituted with aluminum (C-A-S-H). From 20% of fly ash the C-A-S-H phase coexists with sodium aluminosilicate gel N-A-S-H, predominant from 60% of fly ash.